Возможности применения Опросника «7х7» (7 симптомов за 7 дней) для оценки динамики симптомов функциональной диспепсии и синдрома раздраженного кишечника - V. T. Ivashkin; A. A. Sheptulin; Ye. A. Poluektova; D. V. Reykhart; A. V. Belostotsky; A. A. Drozdova; V. S. Arnautov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To study potential of «7×7» questionnaire to assess dynamics of patient’s state throughout treatment course at irritable bowel syndrome (IBS), functional dyspepsia (FD) and combination of these diseases. Material and methods. Original study included 50 patients (36 men and 16 women) aged 18 to 64 years with confirmed diagnoses of IBS, FD and their combination. Basic manifestations of above-mentioned diseases, presence and severity of symptoms initially (visit 1) and their development in 28 days after treatment onset (Visit 2) were estimated by Questionnaire «7×7». Correlation between the results of «7×7» Questionnaire and data of the General clinical impression scale (CGI-s; CGI-i) was evaluated. Results. According to the «7×7» questionnaire most of the patients estimated severity of their state as moderate disorder during the Visit 1. Statistically significant moderate correlation was revealed between the Questionnaire data and General clinical impression scale. During Visit 2, according to attending physician examination (General clinical impression scale), in 40% of patients symptoms have improved. At the same time during Visit 2 according to the «7×7» Questionnaire most of the patients (48%) estimated their state as borderline disorder. Statistically significant moderate correlation similar to that, obtained for Visit 1 was found between results of the Questionnaire and General clinical impression scale. Most of patients and doctors involved in the study highly appreciated convenience of Questionnaire utilization. Conclusions. Application of the «7×7» Questionnaire in clinical practice allows to estimate adequately severity of symptoms of FD and IBS and their dynamics along the treatment process. These results correlate well with results of the General impression scale (CGI-s; CGI-i). Most of the patients and physicians estimate convenience of «7×7» Questionnaire as good or excellent.